2012
DOI: 10.1542/peds.2012-0895
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Stress in Parents on Child Obesity and Related Behaviors

Abstract: The number of parent stressors was directly related to child obesity. Parent-perceived stress was directly related to child fast-food consumption, an important behavioral indicator of obesity risk. Clinical care models and future research that address child obesity should explore the potential benefits of addressing parent stressors and parent-perceived stress.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
136
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 122 publications
(147 citation statements)
references
References 41 publications
9
136
0
2
Order By: Relevance
“…Our finding that chronicity of negative life events is an important predictor of overweight risk requires replication, particularly because 2 previous studies have reported conflicting results, finding greater chronicity associated with both higher 5 and lower 4 overweight risk. Our finding that the association did not differ based on the timing of exposure to negative life events is similar to most 4,7,8 (but not all 9,11 ) previous studies, suggesting that there does not seem to be a developmental window in childhood during which the association of negative life events or stressors with overweight is more robust. Our finding that the maternalreported impact of negative life events was not associated with overweight risk may be consistent with a previous study demonstrating that the objective report of stressors in the home was predictive of child obesity, whereas the parent' s self-reported perceived stress was not.…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…Our finding that chronicity of negative life events is an important predictor of overweight risk requires replication, particularly because 2 previous studies have reported conflicting results, finding greater chronicity associated with both higher 5 and lower 4 overweight risk. Our finding that the association did not differ based on the timing of exposure to negative life events is similar to most 4,7,8 (but not all 9,11 ) previous studies, suggesting that there does not seem to be a developmental window in childhood during which the association of negative life events or stressors with overweight is more robust. Our finding that the maternalreported impact of negative life events was not associated with overweight risk may be consistent with a previous study demonstrating that the objective report of stressors in the home was predictive of child obesity, whereas the parent' s self-reported perceived stress was not.…”
Section: Discussionsupporting
confidence: 86%
“…Psychological and physiologic adaptation to chronic stress, or allostatic load, 1 has important implications for health and disease. The association between psychosocial stressors and risk of childhood obesity has been documented in several studies, [2][3][4][5][6][7][8] although reports have provided less robust support for the association than anticipated, 9 had null findings, [10][11][12][13] or shown evidence of moderation according to age, 9 gender, 4,5 or other factors. 11,12 Improved understanding of the association between psychosocial stress and childhood obesity would inform interventions.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…58 Other parental stressors that influence BMI levels in children include violence, serious life events, food or housing insecurity, maternal depression or substance abuse, and paternal incarceration. [59][60][61][62][63][64][65][66][67] For many studies, SES was a controlled variable in order to determine associations with other psychosocial stressors, but an article by Garasky et al 68 found that financial strain was positively associated with children being overweight or obese.…”
Section: Sleepmentioning
confidence: 99%